Studi Penerapan Manajemen Aset Irigasi pada Daerah Irigasi Nglirip Kabupaten Tuban - Kurniawan, Decka Emeraldi; Prayogo, Tri Budi; Wahyuni, Sri (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Irrigation asset management is required to maintain the condition and function of irrigation assets. The purpose of this study was to determine the priority of rehabilitated assets. As obtained from the results of the inventory survey, the amount of damage in the Nglirip Irrigation Area is 39 points. Physical condition assessment is carried out based on the guidelines of the Ministry of PUPR. Based on the calculation, the main building value is 85,08% (Good), carrier channel is 76,99% (Medium), the complementary building is 80,99% (Medium), Right Nglirip Primary Channel is 81,14 (Good) and Left Nglirip Primary Channel is 79,57% (Medium). The priority scale is calculated by sorting the smallest physical condition values and the AHP method. The order of priority scale based on the physical condition assessment is the carrier channel, Left Nglirip Primary Channel, complementary structure, Right Nglirip Primary Channel and the main structure. The order of priority scale using the AHP method is based on alternatives, the first order is the Right Nglirip Primary Channel, then the Left Nglirip Primary Channel. Meanwhile, based on the criteria, the first order is the carrier channel, the complementary structure and the main structure.